Endothelial dysfunction in development of cerebrovascular disorders in patients with diabetes mellitus - Evgenia Pavlovna Kosobyan (Endocrinology Research Centre, 2012)
Endothelial dysfunction and aberrations of haemostasis play an important part in development of cerebrovascular disorders in patientswith diabetes mellitus. Such factors as hyper- and hypoglycemia, hyperinsulinism, insulin resistance and excessive weight affect progressionof microcirculation deficiency and cerebral ischemia. Transcranial Doppler ultrasound examination is useful as a noninvasivemethod of hemodynamic assessment.